O-023 Characteristics and Outcomes of Acute Ischaemic Stroke Patients Selected and Excluded for Intra-arterial Intervention by Perfusion Imaging. (14th July 2013) - Soltanolkotabi, M; Feiz, F; Beck, C; Rahman, O; Shaibani, A; Hurley, M; Prabhakaran, S; Ansari, S
Abstract : Background/Purpose: Perfusion imaging has been proposed as an effective modality in selecting acute ischaemic stroke (AIS) patients who may benefit from intra-arterial (IA) intervention. We investigated the characteristics and outcomes of patients that were deemed ineligible for IA intervention based on perfusion imaging as compared to those who underwent intervention at our institution. Materials and Methods: A multicentre retrospective review of all AIS patients who underwent perfusion imaging from February 2010 to August 2012 was conducted. Inclusion criteria were the following: symptom-onset to presentation ≤8 hours, anterior circulation large vessel occlusion as determined by CT/MR angiography (MCA/ICA occlusions), baseline National Institute of Health Stroke Scale (NIHSS) score ≥8. Patients selected or excluded for IA intervention based on CT/MR perfusion imaging profiles (CBV/DWI infarct core < 1/3 MCA territory and mismatch of ischaemic penumbra > 20% infarct core) were separated into subgroups for analysis. Patient demographics, cardiac and stroke risk factors, intravenous (IV) tPA utilisation, location of occlusion, time from symptom-onset to presentation, NIHSS and modified Rankin Scores (mRS) scores (baseline, discharge, and 90 days), duration of hospital stay, discharge disposition (home, rehabilitation/nursing home, hospice), and mortality rates were recorded. Good functional outcome was defined as mRS 0–2 at 90 days. Statistical analyses were performed with SPSS 20.0. Results: 110 eligible AIS patients underwent perfusion imaging of which 62 were excluded from IA intervention (56.4%) based on CT/MR perfusion imaging profiles. Table 1 details patient characteristics and outcomes in the intervention versus non-intervention subgroups. Conclusions: Among a large cohort eligible for intervention, perfusion mismatch was present in younger patients with fewer vascular risk factors. These data suggest that advanced age and atherosclerotic risk factors may influence rate of progression from ischaemia to infarction through decreased cerebrovascular reserve and collateral flow in response to arterial occlusion. Despite earlier time to presentation (imaging) and greater receipt of IV tPA, those without perfusion mismatch were deemed futile for IA intervention, six-fold less likely to be discharged to home, and half as likely to have independent functional outcomes. However, nearly one-third of non-intervention patients achieved functional independence at 3 months suggesting the need to refine patient selection strategies for IA intervention. Disclosures: M. Soltanolkotabi: None. F. Feiz: None. C. Beck: None. O. Rahman: None. A. Shaibani: None. M. Hurley: None. S. Prabhakaran: None. S. Ansari: None.